A Biodegradable Stent with Surface Functionalization of Combined‐Therapy Drugs for Colorectal Cancer. Issue 24 (23rd November 2018) - Xie, Xusheng; Zheng, Xiaobin; Han, Zhifen; Chen, Yufeng; Zheng, Zhaozhu; Zheng, Bin; He, Xiaowen; Wang, Yongfeng; Kaplan, David L.; Li, Yi; Li, Gang; Wang, Xiaoqin; et al.
Abstract: In‐stent restenosis caused by tumor ingrowth is a major problem for patients undergoing stent placement because conventional stents often lack sustainable antitumor capabilities. The aim of this work is to develop a silk fibroin (SF)‐based nanofibrous membrane that is loaded with combined‐therapy drugs by using electrospinning technologies, which is further coated on a polydioxanone (PDO) stent and used for the treatment of colorectal cancer (CRC). In order to improve treatment effectiveness, a combination of therapeutic drugs, i.e., curcumin (CUR) and 5‐fluorouracil (5‐FU), is dissolved into SF solution and then eletrospun onto the surface of the PDO stent. The morphology, secondary structure, and in vitro drug release profiles of the membranes are characterized. The antitumor efficacy is assessed in vitro and in vivo using a human CRC cell line and normal cells, and tumor‐bearing nude mice. In vitro and in vivo studies on the nanofibrous memembrane‐coating demonstrate improved antitumor effects for the CUR/5‐FU dual drug system which can be attributed to cell cycle arrest in the S phase in association with induced apoptosis in tumor cells by blocking signal transducer and activator of transcription3 (Stat3) and nuclear factor kappa beta (NF‐kB) signaling pathways, suggesting potential in the treatment of CRC in the future. Abstract : Intestinal obstruction and stenosis are the main symptoms of patients with colorectal cancer. This paper describes a drug‐loaded fibrous silk fibroin (SF) membrane produced by adding curcumin and 5‐fluorouracil into the SF spinning solution for sustained drug release. The membranes as the coating of stent placement have potential in the management of cancer progress and drug‐resistance of tumor cells.